Identification of non-timber forest products marketed in the Viñas Population Center, Pampas, 2023 - Gutiérrez Collao, Jairo Edson (2024)
The objective of the research was to identify the non-timber forest products (NTFP) marketed in the Viñas Population Center. The methodology used was theoretical and analytical, in terms of the type of research it is descriptive and documentary to analyze the current and potential natural resources of the Poblado de Viñas Center. The results show the importance of NTFPs in various conservation and development projects, with emphasis on production and trade in medicinal, ornamental and timber issues, through the evaluation of the different forms of use and sustainability. Finally, it is concluded that the Viñas Population Center reports a great wealth of natural resources, which are essential for the community's economy.